Molecular Fingerprinting and Hybridity Authentication in Cowpea Using Single Nucleotide Polymorphism Based Kompetitive Allele-Specific PCR Assay - Ongom, Patrick Obia; Fatokun, Christian; Togola, Abou; Salvo, Stella; Oyebode, Oluwaseye Gideon; Ahmad, Mansur Sani; Jockson, Ishaya Daniel; Bala, Garba; Boukar, Ousmane (Frontiers in Plant Science, 2021)
Optimization of a breeding program for increased genetic gain requires quality assurance (QA) and quality control (QC) at key phases of the breeding process. One vital phase in a breeding program that requires QC and QA is the choice of parents and successful hybridizations to combine parental attributes and create variations. The objective of this study was to determine parental diversity and confirm hybridity of cowpea F1 progenies using KASP (Kompetitive Allele Specific PCR)-based single nucleotide polymorphism (SNP) markers. A total of 1,436 F1 plants were derived from crossing 220 cowpea breeding lines and landraces to two elite sister lines IT99K-573-1-1 and IT99K-573-2-1 as male parents, constituting 225 cross combinations. The progenies and the parents were genotyped with 17 QC SNP markers via high-throughput KASP genotyping assay. The QC markers differentiated the parents with mean efficiency of 37.90% and a range of 3.4% to 82.8%, revealing unique fingerprints of the parents. Neighbor-Joining cladogram divided the 222 parents into three clusters. Genetic distances between parents ranged from 0 to 3.74 with a mean of 2.41. Principal component analysis depicted a considerable overlap between parents and F1 progenies with more scatters among parents than the F1s. The differentiation among parents and F1s was best contributed to by 82% of the markers. As expected, parents and F1s showed a significant contrast in proportion of heterozygous individuals, with mean values of 0.02 and 0.32 respectively. KASP markers detected true hybridity with 100% success rate in 72% of the populations. Overall, 79% of the putative F1 plants were true hybrids, 14% were false F1 plants, and 7% were undetermined due to missing data and lack of marker polymorphism between parents. The study demonstrated an effective application of KASP-based SNP assay in fingerprinting, confirmation of hybridity, and early detection of selfed plants. The results further uncovered the need to deploy markers as a quality control step in a breeding program.